Genetic divergence of aromatic rice (Oryza sativa L.) - Majumder, Ratna Rani; Roy, Ripon Kumar; Mian, MA Khaleque; Ivy, Nasrin Akter (Bangladesh Journal of Botany, 2018)
Thirty aromatic rice genotypes were studied to assess the nature and magnitude of genetic divergence among them for grain yield and yield contributing characters. Based on 23 characters the genotypes were grouped into 5 clusters. Inter-distances were higher than intra-cluster showing a wide range of genetic diversity among the genotypes of different groups. The highest level of inter-cluster distance (73.48) was found between cluster IV and V. The highest intra-cluster distance (3.364) was computed to cluster V and the lowest 1.851 was observed in cluster IV. Panicle length, days to initial flower opening, spikelet sterility, pollen fertility and harvest index had maximum contribution towards genetic divergence of 30 aromatic rice genotypes. Genotypes having these characters in the genetically distant cluster could, therefore, offer a significant scope for the development of high yielding variety through judicious selection.